USAHA PONDOK WISATA SEBAGAI PENDUKUNG PARIWISATA BUDAYA BERKELANJUTAN DI DESA WISATA UBUD - Agus Wiguna, I Made; Adhika, I Made; Sukma Arida, I Nyoman (JURNAL MASTER PARIWISATA; Volume 05, Nomor 01, July 2018DO - 10.24843/JUMPA.2018.v05.i01.p12, 2018)
Tourism are progressing and even expanding to some remote villages in Bali. Developing a tourist village is considered important since it engages local people in any tourism industry activities. The four elements of tourism, namely: tourist attraction, accessibility, amenities, and ancillary services are “must have” elements for a tourist destination in order to develop tourism in an area. One of the elements namely facilities (amenities) are providing tourists with their needs for accommodation and homestay as an ideal solution for tourist villages to engage local people (community-based tourism) in tourism industries. The purpose of this research is to identify the influence of cottage / homestay business managed by local community to develop a tourist village in Ubud. This study uses the theory of causality (the theory built by cause and effect), and the concept of sustainable tourism. The research method used is qualitative method, and the analysis used is SWOT analysis to identify the influence of homestay on the development of tourist village in Ubud. The results of this study show that the existence of homestay as a main support of sustainable cultural tourism greatly affect the development of tourist villages in Ubud area.